Justification of the choice of excipients for obtaining tablets based on thiotriazoline and paracetamol - Khomyn , Nataliia; Hroshovyi , Taras; Vasenda, Marjana; Plaskonis, Yuliya (The Ukrainian Scientific Medical Youth Journal, 2023)
one of the most frequently used analgesics and antipyretics in the world is paracetamol, despite its hepatotoxicity. The analysis of scientific works showed that common application paracetamol with thiotriazoline decrease in its hepatotoxicity. Pharmacologists offer a combined medicine containing the analgesic-antipyretic paracetamol and thiotriazoline with hepatoprotective action. For the specified combination of paracetamol and thiotriazoline, it is necessary to create a rational dosage form - tablets. To this purpose, it is necessary to select excipients, to investigate their influence on the technological parameters of tablets based on thiotriazoline and paracetamol, to substantiate the choice of the best excipients in the development of a tablet medicinal product. In order to develop the optimal composition of paracetamol tablets with thiotriazoline by wet granulation, the following technological operations were used: sieving, weighing, mixing, moistening, granulation, drying, repeated granulation, powdering and pressing. We used excipients that meet the requirements of the SPhU and ensure the fulfillment of all technological indicators of the quality of tableted drugs. For the implementation of the experiment, mathematical planning was used, namely a five-factor plan based on the Hyper-Greaco-Latin square. In the course of research, the dependence of all studied parameters (mass homogeneity, friability, resistance of tablets to crushing and disintegration time) was determined on auxiliary substances that were included in the composition of tablets based on thiotriazoline and paracetamol according to the selected experimental plan. Technological quality indicators of the obtained tablets, namely Microcrystalline cellulose (MCC) 101, Arbocel P 290, sodium croscarmellose, Aerosil 200, stearic acid, as a binding solution - 5% starch paste